IMPLEMENTASI DEMOKRASI PANCASILA DALAM PEMERINTAH DI INDONESIA - Devra, Desi Devrika; Khairunnisa, Khairunnisa (Jurnal Pengabdian Kompetitif, 2025)
The development of the democratic system in Indonesia began with Representative Democracy which was implemented during the revolution between 1945 and 1950. Furthermore, Indonesia entered the Liberal Democracy era during the Old Order, namely from 1950 to 1959. After that, the government system changed to Guided Democracy which continued in the Old Order era from 1959 to 1966. Then, during the New Order (1966–1998), Indonesia adopted the Pancasila Democracy system. Entering the Reform Order from 1998 to the present, Indonesia adopted the Reform Democracy system. Democracy teaches that because they are the ones who understand their own needs and rights. From this understanding, rules were born that aim to protect and benefit the people. In order for this to be realized, a system of rules is needed that is supported by all parties, which then becomes the foundation in national life in order aprotect the rights of citizens. The rule is manifested in the form of a concept of supreme power in democracy should not be interpreted as something absolute and unlimited. In fact, joint agreement that is stated in the constitution—the result of a joint formulation approved by the people when establishing the state. This constitution is the guideline for channeling, implementing, and managing the sovereignty of the people in the practice of organizing government and daily state life